Heat-Intolerance Syndrome subsequent Foot-and-Mouth Disease in Cattle; ThiQar –Iraq: Adil M. Abbas1 ,Mohammed A. Y. Al-Amery2 , Abbas Y. J. Al-Mousawy2 and Jalel A. Gati1 - Abbas, Adil M. (The Iraqi Journal of Veterinary Medicine, 2012)
The investigation on Heat-Intolerance Syndrome following foot and mouth disease (FMD) infection in cattle in ThiQar–Iraq, used 3ABC FMD ELISA kit, and Radio- immunoassay (RIA) to detect the cortisol level. From 105 there were 65(62%) infected cattle with FMD, which was high at 5- less 8 years old, while the cortrisol level showed three levels; normal (13-21 nmol⁄L), high and low levels were; 6(5.6%), 44(42%) and 55(52%) subsequently. More over the combined result of ELISA and RIA had divided cattle into six groups. First group of 40(38%) cattle infected with FMD and had low level of cortisol, this group containing 21(20%) with clinical signs of heat intolerance. Second group contain 22(21%) FMD infected cattle with high level of cortisol. Third group of 3(2.8%) FMD Infected cattle but normal cortisol level. Fourth group included 3(2.8%) not infected by FMD with normal cortisol level. Fifth group contain 22(21%) not infected with FMD but had high level of cortisol may related to stress. Sixth group consisted 15 (14%) cattle not infected with FMD and had low level of cortisol due to un known cause.Clinical signs of heat intolerance that showed in 21 head of cattle in the first group were: panting, overgrowth of hair coat, emaciation and seeking for shad. The diseased cow known locally as ”Mahrorah” meaning heat-intolerance.